Inflation Persistence in Central and Southeastern Europe: Evidence from Univariate and Structural Time Series Approaches - Mladenović, Zorica; Nojković, Aleksandra (Panoeconomicus, 2012)
The purpose of this paper is to measure inflation persistence in the following countries of Central and Southeastern Europe: Slovakia, the Czech Republic, Poland, Hungary, Romania and Serbia. The study sample covers monthly data from January, 1995 to May, 2010 for Poland, Hungary and Slovakia, from January 1994 to May, 2010 for the Czech Republic, and from January, 2002 to June 2010 for Romania. The shortest sample used, from January, 2003 to September, 2010, was for Serbia and is due to the late start in the transition process. The results of this study enriched the existing ones on this topic by extending the sample period to cover even the recent years of relatively higher inflation rates and by including Romania and Serbia, which were not previously considered. The study led to two main findings: first, inflation of moderate to high magnitude persistence in Hungary, Poland, Romania and Serbia, and inflation of smaller order persistence in Slovakia and the Czech Republic was detected within the Markov switching model approach. In addition, the changes in inflation persistence often correspond to changes in variability and mean of inflation. Second, New Keynesian Phillips Curve represents a valid structural approach to describe the inflation dynamics in this region. In all the six cases studied, weights on backward and forward looking behaviors were significant, while the impact of the driving variable was insignificant only once. It is found that significant influence of the economic driving variable can be captured by real gross wage inflation and real broad money growth. The estimates show that the backward-looking term plays an important role in determining the inflation dynamics. Similar conclusions are drawn by using quarterly data in econometric estimations for the selected countries.Key words: Inflation persistence, Inflation targeting, Markov switching models, The new hybrid Phillips curve model.JEL: E31, E52.